Developing Future Teachers’ Digital Competence While Performing Learning and Research Project - Hrynko, Viktoriia (Pedagogical Discourse, 2019)
The experimental program is aimed at fulfilling the relevant targets of the future primary school teachers’ professional training, in particular forming and developing the digital competence. The author claims that the future teachers’ digital competence is formed as a result of integrating the cognitive, creative, communicative, and collaborative skills. The purpose of the scientific paper is studying the influence of the digital technology on the development of the future primary school teachers’ cognitive, creative, communicative, and collaborative skills while performing learning and research project. In the study the author uses the methods of questionnaire, survey, and observation, as well as the methods of analyzing, comparing, and generalizing the obtained experimental results. While studying the course «Basis of Scientific Research» during the term, the learning and research project «Student Scientific Conference» has been realized. The aim of the project is modelling the process of scientific findings, using the digital technologies for developing the future primary school teachers’ cognitive, creative, communicative, and collaborative skills. When implementing the project, the following forms of working with digital technologies and digital resources have been applied: working on the Internet, working with text editors, working with graphic editors and online services, mutual online cooperation, working with photo and video editors, working on the electronic social networking sites, and involving students from other higher educational institutions in participating in online learning. The research results are presented in the form of comparative analysis of the indicators of the level of development of the future primary school teachers’ cognitive, creative, communicative, and collaborative skills, which are gained at the initial stage (the beginning of the 4th term in the academic year of 2015–2016) and the final stage of research (the end of the 4th term in the academic year of 2015–2016). It is noted that the use of digital technologies at all the stages of the project results in increasing the development of cognitive, creative, communicative, and collaborative skills, which are essential for the future teachers’ professional activities in digital society. The author proposes to introduce the course «Basis of Scientific Research» in the form of learning and scientific project, because such an approach contributes to enhancing the development of digital competence and encourages students to participate in scientific activities.